THE EFFECT OF PRICE AND ADVERTISING ON CONSUMER BEHAVIOR IN THE TIKTOK SHOP MARKETPLACE (Survey of Business Administration Students at the Faculty of Social and Business, International Women's University) - Billy Reihan Yusuf; Dadang Munandar (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to determine the effect of price and advertising on the consumptive behavior of students at Bandung International Women’s University in the TikTok Shop marketplace. The growing trend of consumptive behavior among students is influenced by easy access to social media and digital marketing strategies such as interactive advertisements and discount offers. This research uses a quantitative approach with descriptive and verificative methods. The sample consists of 95 respondents, students of the Business Administration Study Program (2021–2024), selected through proportionate stratified random sampling. Data were collected using questionnaires and analyzed using multiple linear regression through SPSS. The results show that (1) price has a positive and significant effect on students’ consumptive behavior, (2) advertising also has a positive and significant effect, and (3) simultaneously, price and advertising significantly affect consumptive behavior among TikTok Shop users. Therefore, competitive pricing and creative advertising strategies on TikTok Shop have been proven to increase impulsive buying tendencies among students. This research is expected to serve as a reference for digital business practitioners in designing more ethical and educational marketing strategies for young consumers.